The inflammation link between periodontal disease and coronary atherosclerosis in patients with acute coronary syndromes: case-control study - Agnieszka Wojtkowska; Tomasz Zapolski; Joanna Wysokińska-Miszczuk; Andrzej P. Wysokiński (BMC, 2021)
Abstract Background Coronary atherosclerosis and periodontal disease, due to their prevalence, are a serious epidemiological problem. Pathophysiological evidence points to their possible common inflammatory etiopathological background. The aim of the study was to analyze the relationship between the presence and severity of periodontitis, systemic inflammation and selected parameters of myocardial injury and heart function in patients with acute myocardial infarction. Methods The study group consisted of 71 patients 54.22 (7.05)-year-old hospitalized due to acute myocardial infarction. The patients underwent a coronary angiographic examination and echocardiography. The following laboratory parameters were determined: blood morphology, high sensitivity C-reactive protein (hsCRP), erythrocyte sedimentation rate (ESR), fibrinogen, troponin I, creatine kinase myocardial band (CK-MB), brain natriuretic peptide (BNP), lipidogram, glucose, creatinine, glomerular filtration rate (GFR), thyroid stymulating hormone (TSH), glycated hemoglobin (HbA1c). Dental assessment of the patients was performed and the following indicators were included: the number of teeth preserved, approximal plaque index (API), bleeding on probing (BoP), pocket depth (PD), the number of bleeding periodontal pockets ≥ 4 mm in depth (NoPD ≥ 4 mm), the percentage of bleeding periodontal pockets ≥ 4 mm in depth (%PD ≥ 4 mm), clinical attachment loss (CAL). The control consisted of 40 patients 52 (± 8.43)-year-old without a history of coronary heart disease. These patients were subjected to a periodontal examination using the above parameters and classification methods. The following statistical tests were implemented: Shapiro-Wilk test, Levene's test, Mann Whitney's U analysis, Univariate Analysis of Variance (ANOVA); the post-hoc analysis was performed with the use of Tukey's honest significant difference test (HSD), Kruskal-Wallis's non-parametric test, Spearman's rank correlation, logistic regression analysis, linear regression analysis and ROC analysis. Results The BoP (bleeding on probing) significantly correlated with fibrynogen (R-0.36; p-0.006). All indices regarding the pocket depth correlated significantly with the number of leukocytes: PD (R-0.27; p-0.02), NoPD ≥ 4 mm (R-0.28, p-0.02), %PD ≥ 4 mm (R-0.27; p-0.02). PD (R-0.28; p-0.01) and NoPD ≥ 4 mm (R-0.24; p-0.04) were also associated significantly with the level of hsCRP. The BoP is correlated closely with the levels of BNP (R-0.29, p-0.02). The multifactorial analysis showed that significant predictors of myocardial infarction are API and BoP. The analysis showed that API and BoP are important predictors of troponin levels. Linear regression analysis showed that only CAL is a significant predictor of BNP. Conclusions Patients with acute myocardial infarction have worse periodontal status compared to people without coronary heart disease. Greater severity of periodontitis, plaque accumulation and bleeding on probing are associated with acute myocardial infarction. Periodontitis is a risk factor for myocardial infarction and also affects the degree of post-infarction left ventricular damage, which means that there is an inflammatory link between these two diseases.